Without Buddha I could not be a Christian - Knitter, Paul F. (Oxford Oneworld, 2009)
Theologian Paul Knitter tells how Buddhism helped him through a crisis of faith, and explains how Buddhist perspectives can enliven Christianity.
Keywords: Spiritual life -- Christianity. Christian life. Christianity and other religions -- Buddhism